Investigating the Potential Hepatoprotective Effect of Quercetin in Male Rats ‎Following Acute Exposure to Cyclophosphamide - M. Khalaf, Mustafa; A Salih, Rana (The Iraqi Journal of Veterinary Medicine, 2023)
This study aimed to assess the hepatoprotective efficacy of quercetin against ‎hepatotoxicity ‎induced by cyclophosphamide in a rat model. A total of 28 male ‎Wister albino rats (Rattus ‎norvegicus), with body ‎weights ranging from 195.5 to ‎‎198.2 g and approximately three months ‎of age, were randomized into four different ‎groups: the untreated Control group ‎received no interventions; the CYP group was treated with an intraperitoneal ‎injection of ‎cyclophosphamide at a dose of 200 mg/BW; the Qt group received an ‎‎oral administration of quercetin at 100 mg/kg BW daily for ten days; and the combined (Qt+CYP) group received quercetin orally for ten days, followed by a ‎cyclophosphamide ‎injection on the tenth day. Various biochemical markers, ‎including alanine aminotransferase ‎‎(ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and liver glutathione ‎‎(GSH), and malondialdehyde ‎‎(MDA), were analyzed, in addition to body weight and ‎prothrombin time. The ‎Untreated Control group exhibited baseline levels for all assessed ‎markers. In ‎contrast, the CYP group showed elevated levels of ALT, AST, ‎‎ALP, and MDA, coupled with a decrease in GSH. Notably, the Qt+CYP ‎group ‎demonstrated a statistically significant reduction (P‎‎<0.05) in ALT, AST, ALP, ‎and MDA levels, ‎as well as an increase in GSH and prothrombin time, when ‎compared to the CYP group. No significant differences in body ‎weight were observed across all groups ‎‎(P‎‎<0.05). The results of the study indicate that quercetin has the potential to be used as a ‎‎hepatoprotective agent, protecting liver tissues from the cytotoxic effects of cyclophosphamide.